Integrating Interdisciplinary Islamic Studies With Al-Qur'an Based Project Based Learning: Exploring Concepts And Theories In The Context Of Integrated Islamic Schools - Muhammad Al Husaini; Tarmizi Tahir; Zulkarnaen Ali Siddik; Jumadi; M. Nasor (Metakognisi, 2023)
This study aims to explore the integration of Interdisciplinary Islamic Studies with Al-Qur'an-based Project Based Learning (PBL) in education and examine the relationship between relevant concepts and theories. Through an in-depth literature review, this study investigates the core concepts of this approach and how it can be integrated into educational practices within Integrated Islamic Schools.